The Maturity of the Competitive Intelligence Function - João, Gonçalo (2021)
When identifying or comparing organizations with a competitive intelligence function, one should first identify their competitive intelligence systems and then classify the maturity of their competitive intelligence functions. Thispaper presents four different classification levels based on different focus from different authors.